Aedes aegypti breeding site in an underground rainwater reservoir: a warning - Patricia Marques Moralejo Bermudi; Fernanda Kowalski; Marcela Mori Menzato; Millene da Cruz Ferreira; Willian Brendo Silva dos Passos; Vivian Janine Ambriola Oku; Aline Kumow; Taís Vargas Freire Martins Lucio; Tamara Nunes Lima-Camara; Paulo Roberto Urbinatti; Francisco Chiaravalloti Neto (Universidade de São Paulo, 2017)
ABSTRACT We describe the discovery of Aedes aegypti underground breeding site in the Pinheiros neighborhood of São Paulo, SP, during an entomological survey program performed in 2016. Even with intense surveillance and vector control, large numbers of mosquitoes were present in this area. A detailed investigation allowed for the detection of Ae. aegypti in an underground reservoir used for rainwater storage. After the implementation of protection screens in the accesses, the presence of the vector was no longer detected. In this study, we discuss the frequent use of this type of reservoir structure and its risk for mosquito production.